PENERAPAN PEMBELAJARAN CULTURALLY RESPONSIVE TEACHING UNTUK MENINGKATKAN PEMAHAMAN TEKS HIKAYAT PADA SISWA KELAS X SMK NEG. 3 BARRU - Yusuf, Ahmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study investigates the effectiveness of implementing the Culturally Responsive Teaching (CRT) approach in enhancing the comprehension of hikayat texts among 10th-grade vocational high school students. The research problem addresses the challenge of improving students' understanding of cultural texts within a diverse classroom setting. The study employs a Classroom Action Research (CAR) design with two cycles, involving pretest and posttest assessments to measure student learning outcomes. Data were collected from 28 students, with an emphasis on evaluating the impact of CRT on their ability to achieve the Minimum Completeness Criteria (MCC) set at 75. Results from Cycle 1 indicated an improvement in average scores from 65 in the pretest to 72 in the posttest, with the percentage of students meeting MCC increasing from 35.7% to 53.6%. In Cycle 2, after refining the CRT implementation, average scores rose significantly to 80, and the percentage of students achieving MCC reached 78.6%. These findings demonstrate that the CRT approach, which connects instructional content with students' cultural backgrounds, effectively enhances their understanding and engagement with hikayat texts. The study highlights the importance of continuous adjustments to teaching strategies to optimize learning outcomes.